Mendelian randomization study supports the causal association between serum cystatin C and risk of diabetic nephropathy - Feng, Baiyu; Lu, Yu; Ye, Lin; Yin, Lijun; Zhou, Yingjun; Chen, Anqun (Frontiers in Endocrinology, 2022)
Aims: Cystatin C, an inhibitor of cysteine protease, has been used as a biomarker for estimating glomerular filtration rate. However, the causal relation between cystatin C and diabetic nephropathy remains uncertain. Methods: We assessed the causal effect of cystatin C together with other five serum biomarkers including KIM-1, GDF-15, TBIL, uric acid, and Scr on diabetic nephropathy by Mendelian Randomization (MR) analysis. 234 genetic variants were selected as instrumental variables to evaluate the causal effects of cystatin C (NGWAS=361194) on diabetic nephropathy (Ncase/Ncontrol up to 3283/210463). Multivariable MR (MVMR) was performed to assess the stability of cystatin C’s causal relationships. Two-step MR was used to assess the mediation effect of BMI and SBP. Results: Among the six serum biomarkers, only cystatin C causally associated with diabetic nephropathy (IVW OR: 1.36, 95%CI [1.15, 1.61]). After adjusting with the potential confounders BMI and SBP, Cystatin C maintained its causal effect on the DN (OR: 1.17, 95%CI [1.02, 1.33]), which means that the risk of DN increased by 17% with an approximate 1 standard deviation (SD) increment of serum cystatin C level. Two-step MR results indicated that BMI might mediate the causal effect of cystatin C on diabetic nephropathy. Interpretation: Our findings discovered that cystatin C was a risk factor for diabetic nephropathy independent of BMI and SBP in diabetes mellitus patients. Future research is required to illustrate the underlying mechanism and prove targeting circulating cystatin C could be a potential therapy method.